Phase-field modeling of γ/γ″ microstructure formation in Ni-based superalloys with high γ″ volume fraction. (May 2020) - Schleifer, Felix; Holzinger, Markus; Lin, Yueh-Yu; Glatzel, Uwe; Fleck, Michael
Abstract: The excellent mechanical properties of the Ni-based superalloy IN718 mainly result from coherent γ″ precipitates. Due to a strongly anisotropic lattice misfit between the matrix and the precipitate phase, the particles exhibit pronounced plate-shaped morphologies. Using a phase-field model, we investigate various influencing factors that determine the equilibrium shapes of γ″ precipitates, minimizing the sum of the total elastic and interfacial energy. Upon increasing precipitate phase fractions, the model predicts increasingly stronger particle-particle interactions, leading to shapes with significantly increased aspect ratios. Matching the a priori unknown interfacial energy density to fit experimental γ″ shapes is sensitive to the phase content imposed in the underlying model. Considering vanishing phase content leads to 30 % lower estimates of the interfacial energy density, as compared to estimates based on realistic phase fractions of 12 % . We consider the periodic arrangement of precipitates in different hexagonal and rectangular superstructures, which result from distinct choices of point-symmetric and periodic boundary conditions. Further, non-volume conserving boundary conditions are implemented to compensate for strains due to an anisotropic lattice mismatch between the γ matrix and the γ″ precipitate. As compared to conventional boundary conditions, this specifically tailored simulation configuration does not conflict with the system's periodicity and provides substantially more realistic total elastic energies at high precipitate volume fractions. The energetically most favorable superstructure is found to be a hexagonal precipitate arrangement. Graphical abstract: Image 1 Highlights: Particle-particle interaction in specifically tailored periodic superstructures. Finite γ″ phase content leads to significantly altered precipitate shapes. A hexagonal γ″ precipitate arrangement is energetically most favorable. A γ / γ ″ interface energy of 90–200 mJ m −2 fits best to experimental data.